Back Cover. Issue 1 (18th December 2022) - Unknown
Abstract : Soft, environmentally degradable microfluidic devices for sweat collection and colorimetric analysis of biomarkers. These environmentally friendly wearable microfluidic platforms can monitor sweat loss, sweat rate, pH, and chloride concentration during physical activities, with the ability to biodegrade naturally in the soil or in industrial composting facilities to yield end products with beneficial uses as fertilizers and species to improve soil health. Abstract : Soft, environmentally degradable microfluidic devices for sweat collection and colorimetric analysis of biomarkers. These environmentally friendly wearable microfluidic platforms can monitor sweat loss, sweat rate, pH, and chloride concentration during physical activities, with the ability to biodegrade naturally in the soil or in industrial composting facilities to yield end products with beneficial uses as fertilizers and species to improve soil health.